Complexin Controls Spontaneous and Evoked Neurotransmitter Release by Regulating the Timing and Properties of Synaptotagmin Activity - Jorquera, Ramon A. (Society for Neuroscience, 2012)
Neurotransmitter release following synaptic vesicle (SV) fusion is the fundamental mechanism for neuronal communication. Synaptic exocytosis is a specialized form of intercellular communication that shares a common SNARE-mediated fusion mechanism with other membrane trafficking pathways. The regulation of synaptic vesicle fusion kinetics and short-term plasticity is critical for rapid encoding and transmission of signals across synapses. Several families of SNARE-binding proteins have evolved to regulate synaptic exocytosis, including Synaptotagmin (SYT) and Complexin (CPX). Here, we demonstrate that Drosophila CPX controls evoked fusion occurring via the synchronous and asynchronous pathways. cpx(−/−) mutants show increased asynchronous release, while CPX overexpression largely eliminates the asynchronous component of fusion. We also find that SYT and CPX coregulate the kinetics and Ca(2+) co-operativity of neurotransmitter release. CPX functions as a positive regulator of release in part by coupling the Ca(2+) sensor SYT to the fusion machinery and synchronizing its activity to speed fusion. In contrast, syt(−/−); cpx(−/−) double mutants completely abolish the enhanced spontaneous release observe in cpx(−/−) mutants alone, indicating CPX acts as a fusion clamp to block premature exocytosis in part by preventing inappropriate activation of the SNARE machinery by SYT. CPX levels also control the size of synaptic vesicle pools, including the immediate releasable pool and the ready releasable pool—key elements of short-term plasticity that define the ability of synapses to sustain responses during burst firing. These observations indicate CPX regulates both spontaneous and evoked fusion by modulating the timing and properties of SYT activation during the synaptic vesicle cycle.